2022
DOI: 10.1111/1759-7714.14287
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemotherapy, extent of resection, and immunoistochemical neuroendocrine markers as prognostic factors of early‐stage large‐cell neuroendocrine carcinoma

Abstract: Background We investigated whether adjuvant chemotherapy, extent of resection, and immunoistochemical neuroendocrine markers affected survival of patients with the early stage of large‐cell neuroendocrine cancer. Methods This was a retrospective multicenter study including consecutive patients undergoing resection of node negative large‐cell neuroendocrine carcinoma. Five‐year survival and disease‐free survival rate were evaluated by the Kaplan–Meier method and the log‐rank test in relation to adjuvant chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Hu et al [ 19 ] found that patients with stage IA LCLC did not benefit from postoperative chemotherapy for OS, whereas in patients with stages IB and II, postoperative chemotherapy patients had better OS than those who had surgery alone. On the contrary, some previous studies indicated that chemotherapy was beneficial to the survival of stage I lung cancer patients [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 93%
“…Hu et al [ 19 ] found that patients with stage IA LCLC did not benefit from postoperative chemotherapy for OS, whereas in patients with stages IB and II, postoperative chemotherapy patients had better OS than those who had surgery alone. On the contrary, some previous studies indicated that chemotherapy was beneficial to the survival of stage I lung cancer patients [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 93%
“…Chemotherapy in well-differentiated G1/G2/G3 NEN usually does not improve significantly and can cause many adverse events and deterioration of the quality of life. Recommended regimens for chemotherapy are mostly two-component approaches, i.e., streptozocin (STZ) with 5-fluorouracil (5-FU) or doxorubicin (DOX); cisplatin (P) with etoposide (E); or capecitabine with temozolomide (CAPTEM) [4,[32][33][34][35]. It is essential to note that local drug availability, comorbidities, and patient clinical conditions and expectations can also limit this kind of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…It is administered in four courses (administrations) at 8-week intervals; treatment maintenance is conducted with a long-acting somatostatin analogue (lanreotide 120 mg or octreotide 30 mg) every 4 weeks [ 20 , 21 ]. The other therapeutic options for patients with NEN include chemotherapy, which is preferred for tumors with a higher proliferation index (Ki-67), such as NEN G3 or neuroendocrine carcinomas (NECs), with a recommended two-component scheme such as capecitabine plus temozolomide (CAPTEM) or carboplatin plus etoposide [ 14 , 22 , 23 , 24 , 25 ]. Equivalent therapeutic options are targeted therapies: tyrosine kinase inhibitor (TKI)—sunitinib or a selective inhibitor of m-TOR (mammalian target of rapamycin)—everolimus, However, they are limited by possible complications and side effects [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%